Comparative osteomorphological criteria for differentiating mandibular teeth and post-cranial skeletons of takins (Budorcas taxicolor) from Bovini species on Tibetan Plateau - Zhang, Zhengwei; Li, Fan; Marshall, Fiona (Frontiers in Ecology and Evolution, 2022)
For centuries, hunting and herding of large bovids were important for human survival at high altitudes on the Tibetan Plateau. However, little is known about past human relations with iconic plateau animals, such as takins (Budorcas taxicolor Hodgson, 1850) or yaks (Bos grunniens Linnaeus, 1766). Takins were widely hunted historically for subsistence and social reasons, but an understanding of ancient relationships has been hampered by the difficulty of distinguishing takins from other large wild or domestic bovids, e.g., gaurs (Bos gaurus), yaks, cattle (Bos taurus), water buffalo (Bubalus bubalis). Through the comparative and systematic study of modern specimens, comprising 80 mandibles and 53–78 skeletons curated across five institutions in China and the United States, this research proposes a new set of osteomorphological criteria for differentiating large bovids from the Tibetan Plateau and tests previously published criteria. The results show that takins can be easily differentiated from yaks, cattle, gaurs, and water buffalos using readily identifiable shape differences, non-metric characteristics, and specific landmarks of mandibular teeth and post-cranial elements. Criteria with especially high-reliability scores include mandibular teeth and 14 postcranial elements: scapula, humerus, femur, tibia, fibula, metapodials, lunate, scaphoid, magnum, unciform, and astragalus. Providing a reproducible field method for distinguishing takins from other large bovids in this region, the osteomorphological criteria established in this study will further archaeological investigations of Holocene hunting on the Tibetan Plateau, as well as early usage of domesticated yaks and cattle. These criteria can also be used in conservation to aid field identification of illegally hunted takins.